Cigarette smoke extract induces differential expression levels of beta-defensin peptides in human alveolar epithelial cells - Tony Pierson; Sarah Learmonth-Pierson; Daniel Pinto; Monique L van Hoek (Tobacco Induced Diseases, 2013)
Background The damaging effects of cigarette smoke on the lungs are well known in terms of cancer risks. Additional molecular changes within the lung tissue can also occur as a result of exposure to cigarette smoke. The human β-defensin (hBD) class of antimicrobial peptides is the focus of our research. In addition to antimicrobial activity, β-defensins also have immunomodulatory functions. Over 30 previously unrecognized β-defensin genes have recently been identified in the human genome, many with yet to be determined functions. We postulated that altered β-defensin production may play a role in the pathogenesis observed in the lungs of smokers. Our hypothesis is that cigarette smoke exposure will affect the expression of β-defensins in human lung alveolar epithelial cells (A549).